Design of a traveling wave thermo‐acoustic engine based on genetic algorithm. (12th August 2019) - Zare, Shahryar; Tavakolpour‐Saleh, AliReza
Summary: This paper presents a novel design scheme for traveling wave thermo‐acoustic Stirling engines (TASEs) based on a target frequency using genetic algorithm (GA). First, the effects of engine design parameters on the system performance are studied via root locus method. Accordingly, it is found that the resonator length, the inertance diameter, and the hot gas temperature are the most effective parameters in the engine design procedure. Next, the relation between the closed‐loop poles positions of the thermo‐acoustic system and the effective design variables are described parametrically. Consequently, in order to estimate the optimum values of the effective design parameters as well as the unknown positions of the nondominant poles, an appropriate fitness function based on the desired engine frequency is proposed. Subsequently, a GA is used to achieve the optimal values of design parameters so as to minimize the considered cost function. Finally, the validity of the proposed design technique is verified by comparing the obtained results with the available data of an experimental case study.